The trajectory of teacher education offered at the Open University of Brazil-UAB in São Mateus-ES and the view of the graduates (Research, Society and Development, 2020)
A case study was accomplished to analyze the contributions and challenges of the Brazilian distance learning program (open University of Brazil-UAB) on teacher training. Besides, it was presented an overview of the consolidation of Polo UAB and the municipal demand for teacher training. Based on data analysis, it could be noted that courses were not offered to meet the required demand of the municipality. It was noted that former students from Polo UAB were approved in the last public contest to work in municipal and state government. Data analysis of a survey form, answered by tutors, showed high drop-out rates. These mainly refer to the student’s issues and student’s lack of time to accomplish commitments previously scheduled by the distance learning program. It was also noted that there were not enough incentives either to open new courses handling with the teacher training or to maintain the offers for vacancies in the existing courses. In the Brazilian distance learning program (Polo UAB), preventive strategies to assure student presence in the courses and instruments to indicate student absences were lacking.